A millennial mindset: how modal shift affects the transportation choices of university students - Weber, Jessica (Kansas State University, 2016)
Growing urban populations and the increasing prevalence of the millennial generation are profoundly changing personal travel behaviors and patterns. As a result, cities, planners, and developers must understand and act upon the shifting preferences and expectations of these public transit users in order to align costly public transit services with user needs in efficient ways. While public transit systems are becoming an increasingly vital part of urban life, few jurisdictions have considered the need to tailor these systems to millennials – those most likely to incorporate public transit into their daily lives. This paper examines the travel behaviors of University Students engaged in a forced travel intervention caused by a sudden relocation of their work site. The change in work location encouraged the use of a free public transit system as means of commuting. Longitudinal survey results, taken pre and post-intervention, indicate statistical differences between transit preferences and actual habits related to transit use and other modes of travel. Survey findings suggest that there is a statistically significant difference between the stated willingness and actual travel behaviors of public transit users and of drivers, and that modal shifts can assist in overcoming the attitude/behavior split related to personal travel among millennials.
Keywords: Modal shift; Millennials; Intervention; Transit; Preferences; Policy